A Validitas Laboratorium Virtual Filasik sebagai Materi Suhu dan Peneraan Termometer - Ganiestya Catur Adi Kertanegara; Mita Anggaryani (PendIPA Journal of Science Education, 2023)
Virtual laboratory is useful as an alternative to real laboratory where virtual laboratory can provide facilities that are not available in real laboratory and help prepare students for real experiences in real laboratory. This study aimed to determine the validity of the Filasik virtual laboratory media. The research model used is the ADDIE development model (analysis, design, development, implementation, and evaluation) and the phases carried out up to the development phase. In the analysis phase, a needs analysis was carried out which consists of the needs of students and laboratory facilities. In the design phase, product design was carried out using HTML5 <canvas> with the javascript programming language. In the development phase, product development is carried out and tested on expert validators. The validation sheet consists of 4 aspects, namely display aspect, navigation aspect, program operation aspect, and usability aspect. The results of the validation assessment of the developed Filasik virtual laboratory were 95% and had very good qualifications and valid description with the reliability of validation results of 97%. So, the Filasik virtual laboratory is valid for use in learning on temperature material and thermometer measurements.